Phenothiazines enhance antibacterial activity of macrophage by inducing ROS and autophagy - Qiu, Lihao; Chen, Wen; Wang, Jianfeng; Deng, Xuming; Liu, Hongtao; Qiu, Jiazhang (Frontiers in Immunology, 2025)
Bacterial infections pose a major global public health threat. While antibiotics have historically served as the primary treatment, the rapid rise of antibiotic resistance has led to an urgent need for new therapeutic strategies. Host-directed therapies (HDTs), which activate defense mechanisms of host cells, are emerging as a promising alternative. Host-acting compounds (HACs) have no direct effect on bacteria and therefore do not induce drug resistance or alter intestinal microbiota composition. In the present study, we demonstrated that phenothiazines significantly enhance the antibacterial capacity of macrophages. In macrophages treated with phenothiazines, we observed a significant increase in lysosomal activity, induction of autophagy, and accumulation of reactive oxygen species (ROS). Importantly, co-treatment with autophagy inhibitors or ROS scavengers markedly diminished the antibacterial effects of phenothiazines. Furthermore, perphenazine (PHZ) effectively reduced organ lesions and inflammation associated with S. Typhimurium infections in vivo. Our results demonstrated that phenothiazines are lead compounds for antibacterial agents via HDTs.